2013
DOI: 10.3109/0886022x.2013.859528
|View full text |Cite
|
Sign up to set email alerts
|

CA 125 levels and left ventricular function in patients with end-stage renal disease on maintenance hemodialysis

Abstract: Purpose: The aim of this study was to analyze associations between serum cancer antigen 125 (CA 125) levels and left ventricular (LV) function in patients with end-stage renal disease on maintenance hemodialysis (HD). Methods: CA 125 levels, pro-brain natriuretic peptide (pro-BNP) and biochemical parameters were measured, and echocardiography was performed for 110 patients and 47 healthy controls. Results: The mean CA 125 level in patients, 38.78 AE 35.48 U/ mL, was significantly higher than that found in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…CEA, SCC, NSE, S-100, and PSA) in the presence of decreased kidney function, since these parameters showed a high false-positive rate, and thus were unreliable for monitoring malignancies in uremic patients [65][66][67]. In a very recent paper, CA125 levels were modified by impaired left ventricular function in patients with end-stage renal diseases [68]. In our own study [69], elevated HE4 levels could already be measured at early stages of chronic kidney disease (CKD), while CA125 values were significantly higher compared to healthy individuals only in CKD4-5, suggesting that CA125 was less affected by estimated glomerular filtration rate (eGFR) than HE4.…”
Section: The Association Of He4 With Renal Functionmentioning
confidence: 95%
“…CEA, SCC, NSE, S-100, and PSA) in the presence of decreased kidney function, since these parameters showed a high false-positive rate, and thus were unreliable for monitoring malignancies in uremic patients [65][66][67]. In a very recent paper, CA125 levels were modified by impaired left ventricular function in patients with end-stage renal diseases [68]. In our own study [69], elevated HE4 levels could already be measured at early stages of chronic kidney disease (CKD), while CA125 values were significantly higher compared to healthy individuals only in CKD4-5, suggesting that CA125 was less affected by estimated glomerular filtration rate (eGFR) than HE4.…”
Section: The Association Of He4 With Renal Functionmentioning
confidence: 95%
“…The results of this study showed that CA-125 may be a useful biomarker to be addressed in CKD patients on hemodialysis with systolic HF. In a previous study (10) including 110 maintenance hemodialysis patients and 47 healthy controls, mean CA-125 levels in hemodialysis group (38.7 U/mL) was significantly higher in comparison to healthy subjects (9.2 U/mL; P = 0.003). This contradicts our findings as we did not find significant difference regarding CA-125 between hemodialysis and healthy subjects.…”
Section: Discussionmentioning
confidence: 71%
“…This contradicts our findings as we did not find significant difference regarding CA-125 between hemodialysis and healthy subjects. The authors (10), then divided the hemodialysis group (based on CA-125 level of 26.6 U/mL) into two groups. Those with CA-125 levels of more than 26.6 U/mL had significantly higher LVESD and LVEDD and lower LVEF (32% vs. 59%).…”
Section: Discussionmentioning
confidence: 99%
“…Another marker, cancer antigen 125 (CA125), emerged in the literature as positively and consistently associated with a higher risk of 1-year all-cause and cardiovascular mortality throughout the whole spectrum of eGFR categories, independent of kidney function [ 60 ]. Serum CA125 levels are also associated with LV dysfunction in hemodialysis patients [ 68 ].…”
Section: Human Biomarkers Of Cardiovascular Risk In Ckdmentioning
confidence: 99%